MAKAN ADAT DALAM UPACARA PEMINANGAN LAKI-LAKI SUKU ABUI KEPADA PEREMPUAN SUKU KUI DI KABUPATEN ALOR - Intan Permatasari Lema Madde; Herlofina Manikafola; Heronike Mangmani; Neziah Hinagay, Inggrit E. Bayang, Henderina Womakal, Inang Naila Mustapa, Imanuel Laukamang, Halena (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2025)
The purpose of this study is to examine traditional food in the betrothal ceremony of Abui men to Kui women in Alor Regency. This study uses a qualitative method with an ethnographic approach. Data analysis techniques are carried out by means of data reduction and drawing conclusions. The research was conducted in Matalafang Tourism, Lembur Barat Village, North Central Alor District, Alor Regency. The informant in this study was the Matalafang traditional leader. The result of this study is the traditional meal in the betrothal of Abui men to Kui women. One of the customs that is still maintained today is the traditional meal in the betrothal ceremony of men to women. The betrothal of Abui men to Kui women is part of the marriage procession of the Abui and Kui communities. In conducting the engagement ceremony, both parties are represented by their respective spokespersons. In general, the traditional meals of the Abui and Kui tribes in the engagement ceremony are similar, where families bring rice and animals.